Correlation and capability of using site inspection data and small specimen creep testing for a service-exposed CrMoV pipe section - Cacciapuoti, Bianca; Morris, A.; Sun, Wei; McCartney, D.G.; Hulance, J. (Taylor & Francis, 2018)
This paper presents for the first time an investigation on the creep damage evolution of an ex-service CrMoV pipe section through impression creep test and metallurgical inspection data. The study emphasises the importance of correlating the operating conditions (temperature and stress) of power plant components with the results from metallurgical examinations and small specimen creep tests.